Fatigue life characterization and modeling of a Ni–Ti snake-like element for mini actuation. (17th August 2020) - Nespoli, Adelaide; Berti, Francesca; Petrini, Lorenza; Pennati, Giancarlo; Villa, Elena; Passaretti, Francesca
Abstract: The interest in the design of shape memory alloy (SMA) actuators is recently broadened thanks to their high power density and versatility. In particular, snake-like Ni–Ti actuators demonstrated high potential at the mini- and micro-scales as SMA non-conventional active elements, due to their capacity to provide significant displacements in a very limited space and over a high number of thermo-mechanical cycles. In this study, the fatigue behavior of a snake-like Ni–Ti element has been investigated to identify the Wöhler F-N curve. Moreover, a validated digital twin of the device was prepared and used to evaluate the stress distribution throughout the fatigue tests, to convert the experimental data into a Wöhler stress-life curve. The numerical description of shape memory behavior was performed through the Petrini–Bertini constitutive model, which also allowed a better insight for future shape and functional optimization of the device.